Pregnancy-induced rhinitis: nose problems at the obstetrician’s office - Standyło, Arkadiusz; Obuchowska, Aleksandra; Obuchowska, Karolina; Gorczyca, Kamila; Kimber-Trojnar, Żaneta; Leszczyńska-Gorzelak, Bożena (Journal of Education, Health and Sport, 2022)
Introduction and purpose Pregnancy-induced rhinitis (PIR) manifests as nasal congestion, with resolution of symptoms after delivery. Pregnancy-induced rhinitis is a distinct condition from allergic rhinitis, it may not respond to treatment for allergic rhinitis. The first stage in providing adequate and effective management of PIR is to have a clear and appropriate diagnosis. Therefore, each patient-specific management of PIR must take careful consideration of a variety of circumstances. The aim of this study was to conduct a literature review on pregnancy-induced rhinitis. A literature review was carried out in the PubMed, MEDLINE, and Scopus databases using the terms ‘rhinitis and pregnancy’. Brief description of the state of knowledge Physiological factors underlying PIR are not well understood at the moment. There is no single explanation for the pathophysiological mechanism that would account for the changes in PIR. Nasal congestion is the primary nasal symptom in pregnancy-induced rhinitis. It can result in night-time mouth breathing and poor sleep quality. The mother’s sleep may be negatively impacted by nasal congestion resulting in maternal hypertension, pre-eclampsia, and intrauterine growth retardation. Increasing awareness not only benefits pregnant patients’ quality of life but also has a favourable impact on how a pregnancy turns out. Summary PIR has gained relevance in recent years due to its major effects on maternal quality of life as well as the identification of a relationship with OSAS in the mother and potential harmful consequences on the foetus. The mother’s quality of life is significantly impacted by PIR, as shown, thus both the otorhinolaryngologist and the obstetrician must use caution in the early identification and treatment of pregnancy-induced rhinitis.